Theory of magnetic neutron and photon scattering - Balcar, Ewald (Oxford University Press, 1989)
This book provides an account of the calculation of the matrix elements of the magnetic interaction operator, extracting important, useful results from mathematical analysis. The authors give a complete theory of nonrelativistic magnetic neutron scattering with various tables listing nj symbols, fractional parentage coefficients, and various other quantities that arise naturally in the theory. Subsequently, the book takes account of the growing interest in magnetic photon scattering realized by synchrotron photon factories and contains an appropriate theory. While the treatment centers on scattering from atomic electrons, scattering from conduction electrons is also covered